Drought-stressed, irrigated, and additive-treated corn silages for growing cattle - K. Bolsen; H. Ilg; R. Smith; J. Hoover; D. Axe (Kansas Agricultural Experiment Station Research Reports, 1985)
Cattle fed drought-stressed corn silage gained about 10% slower but were just as efficient as cattle fed irrigated corn silage. Because the irrigated corn out yielded the drought corn (17.4 VS. 8.2 tons per acre), the irrigated silage gave a much higher cattle gain per acre (1928 VS. 940 1b). Silo Guard II®-treated silage had an advantage in DM recovery and feed conversion over its control and produced 4.6 more pounds of cattle gain per ton of crop ensiled. Cattle fed H/M Inoculant®- treated silage gained significantly faster than cattle fed the control, however, the treated silage gave only slight improvements in DM recovery and gain per ton of crop ensiled.
Keywords: Cattlemen' s Day; 1985; Kansas Agricultural Experiment Station contribution; no. 85-319-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 470; Beef; Corn silage; Gain; Yield